PENGARUH RESISTANCE TO CHANGE TERHADAP PRESTASI BELAJAR MAHASISWA (STUDI EMPIRIS PADA MAHASISWA UNIVERSITAS SWASTA X DI JAKARTA) - Ayu Dwi Nindyati (Universitas Paramadina, 2014)
The research purpose is understanding the effect of resistance tochange (RTC) on academic performance. Generally RTC is one of theindustrial and organizational (I/O) phenomena. As in I/O, student’s RTC isexpected to affect student’s academic performance, as employee performancein I/O setting. The concept of RTC in this research is concept from Oreg(2003) that has four dimensions (short term thinking, emotional reaction toimposed change, routine seeking and cognitive rigidity). Student’s academicperformance in this research was cumulative performance index (CPI). Thiswas a quantitative research with 31 respondents for pilot study and 70respondents for field study. Data analysis used correlation analysis andmultiple-regression (step wise method). The results show that RTC wasrelated to academic achievement. Multiple regression analysis showed thatonly emotion reaction to imposed change of RTC had an effect on academicachievement.